2013
DOI: 10.1104/pp.113.216481
|View full text |Cite
|
Sign up to set email alerts
|

The Initiation of Epigenetic Silencing of Active Transposable Elements Is Triggered by RDR6 and 21-22 Nucleotide Small Interfering RNAs    

Abstract: Transposable elements (TEs) are mobile fragments of DNA that are repressed in both plant and animal genomes through the epigenetic inheritance of repressed chromatin and expression states. The epigenetic silencing of TEs in plants is mediated by a process of RNA-directed DNA methylation (RdDM). Two pathways of RdDM have been identified: RNA Polymerase IV (Pol IV)-RdDM, which has been shown to be responsible for the de novo initiation, corrective reestablishment, and epigenetic maintenance of TE and/or transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
333
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(355 citation statements)
references
References 51 publications
(72 reference statements)
17
333
0
5
Order By: Relevance
“…In rice, 24-nucleotide lmiRNAs generated by coordinated actions of DCL1 and DCL3 are associated with AGO4 to direct DNA methylation in trans at the miRNA target genes, resulting in TGS in some cases (Wu et al, 2010). In addition to AGO4 that functions in the canonical RdDM pathway, AGO2 and AGO6 can also mediate de novo DNA methylation by recruiting 21-to 22-nucleotide siRNAs, which are processed from Pol II/RDR6-dependent dsRNAs by DCL2 and DCL4 Marí-Ordóñez et al, 2013;Nuthikattu et al, 2013).…”
Section: Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…In rice, 24-nucleotide lmiRNAs generated by coordinated actions of DCL1 and DCL3 are associated with AGO4 to direct DNA methylation in trans at the miRNA target genes, resulting in TGS in some cases (Wu et al, 2010). In addition to AGO4 that functions in the canonical RdDM pathway, AGO2 and AGO6 can also mediate de novo DNA methylation by recruiting 21-to 22-nucleotide siRNAs, which are processed from Pol II/RDR6-dependent dsRNAs by DCL2 and DCL4 Marí-Ordóñez et al, 2013;Nuthikattu et al, 2013).…”
Section: Dna Methylationmentioning
confidence: 99%
“…It was also shown that AGO4 and AGO6 differ in their subnuclear colocalization and in interactions with Pol II and Pol IV, and it was proposed that they may act sequentially to mediate DNA methylation . AGO6 also binds RDR6-dependent 21-to 22-nucleotide siRNAs generated from transcriptionally active TEs and is thought to trigger the initiation of de novo TE DNA methylation (Nuthikattu et al, 2013;McCue et al, 2015), which may provide a link between PTGS and TGS of TEs.…”
Section: Ago2/3/7 Cladementioning
confidence: 99%
“…Pol IV-dependent siRNAs are often produced from transposable elements (TEs), TE-like sequences, and other repeats (Zhang et al, 2007;Mosher et al, 2008). They contribute to the reinforcement of TE silencing (Slotkin et al, 2005;Marí-Ordóñez et al, 2013;Nuthikattu et al, 2013) and in some cases are also essential to control the expression of proteincoding genes in cis or in trans (Liu et al, 2004;Kinoshita et al, 2007;McCue et al, 2013).…”
mentioning
confidence: 99%
“…This suggests that a threshold regulation is involved in epigenetic switches at E-TELs. In contrast, transposable element families naturally targeted by RDR6-RdDM, such as AtREP10C (part of the HELITRON superfamily) and ROMANIAT5 (Nuthikattu et al, 2013), were consistently found among R-TELs in our analyses (Appendix Figs S11 and S12). This opens the possibility that TEs naturally able to produce RDR6-dependent sRNAs cannot stably switch to demethylated epialleles and would thus be in the R-TELs category.…”
Section: Discussionmentioning
confidence: 74%
“…That E-TELs might be stimulated to acquire DNA methylation when particular mechanisms involved in restoration of "silent locus identity" are locally reinforced is an interesting concept. Recent studies have revealed an alternative RdDM pathway involving 21-to 22-nt sRNAs and RNA-dependent RNA polymerase 6 (RDR6), known as RDR6-RdDM, that separates initiation of de novo DNA methylation and silencing from its maintenance (Nuthikattu et al, 2013;Bond & Baulcombe, 2015). It has been demonstrated that the lost DNA methylation at the FWA promoter, a typical and frequently studied E-TEL, can be reversed when additional 21-to 22-nt sRNAs are provided through a viral vector (Bond & Baulcombe, 2015).…”
Section: Discussionmentioning
confidence: 99%